Molecular characterization of caimito in the state of Morelos - Andrade-Rodríguez, María; Rodrìguez Rojas, Teresa de Jesùs; Villegas-Torres, Oscar G.; Castillo Gutiérrez, Antonio (Revista Mexicana de Ciencias Agrícolas, 2021)
The fruit growing of Mexico has 63 commercial species and 220 species with food potential. In the state of Morelos, 1.7 ha of caimito have been reported in the municipalities of Coatlán del Río and Tetecala de la Reforma. Caimito is an alternative source for the diversification of agriculture, as well as for fruit export. The knowledge of the genetic variability of the species will allow the development of programs oriented to the conservation of germplasm in situ or ex situ, certification programs, as well as provide producers with a wide selection of plants. The objective of the study was to molecularly characterize previously selected caimito trees in Coatlán del Río and Tetecala de la Reforma, Morelos, Mexico, using the RAPDs technique. Thirteen caimito trees were selected considering the morphological and organoleptic characteristics for the selection. Genomic DNA isolation was performed, and 30 RAPD primers were used. Molecular data were processed using the numerical taxonomy and multivariate analysis system (NTSYSpc 2.1). The methodology used allowed the characterization of nine trees. The cluster analysis obtained shows that at a level of 0.71 of genetic distance, four groups form. Trees 14 and 15 do not share genetic similarity with the other trees and these were in turn the ones that showed the greatest number of marker bands and were also some of those that stood out for their flavor.